The Kessler psychological distress scale: translation and validation of an Arabic version - Scott D. Easton; Najwa S. Safadi; Yihan Wang; Robert G. Hasson (Health and Quality of Life Outcomes, 2017)
Abstract Background The Kessler Psychological Distress Scale has been widely used in assessing psychological distress among general and clinical populations from different cultural backgrounds. To our knowledge, however, researchers have not yet validated any translated versions in Arabic. The purpose of this study was to test the reliability and validity of Arabic translations of the ten item (K10) and six item (K6) versions among public sector employees in the Occupied Palestinian Territories. Methods As part of a larger research project on life satisfaction, researchers collected data from 234 Palestinian social workers in June and July of 2016. The survey included several mental health measures, including the K10, which were translated from English to Arabic by an experienced language expert. In the current study, we tested reliability by measuring internal consistency using Cronbach’s alpha coefficient. Next, we assessed factor structure using variance-covariance matrix with maximum likelihood estimation. Confirmatory factor analysis was performed to examine three competing models: unidimensional K10 model, unidimensional K6 model and two-factor K6 model. Fit indices and parameter estimates were reported. Last, convergent validity was examined by assessing correlations with Generalized Anxiety Disorder (GAD-7) and Somatic Symptoms Scale (SSS-8). Results The mean scores for the K6 and K10 were, respectively, 12.87 (SD = 4.02) and 21.8 (SD = 6.7), indicative of mild to moderate levels of distress. Scale reliability analysis showed satisfactory results on both K6 and K10 versions (Cronbach’s α = .81 (K6) and .88 (K10)). Among three competing models, the two-factor K6 scale demonstrated the best model fit with high factorial correlations (r = .60, p < .001). Moreover, the K6 has high convergent validity with GAD-7 (r = .66, p < .001) and SSS-8 (r = .61, p < .001). Conclusion Results indicated that the translated version of the two-factor K6 scale is a valid and reliable measurement of psychological distress. Our findings suggest that practitioners and researchers can use this instrument in screening and assessing psychological symptoms with Arabic-speaking populations.